Is there a role for bisphosphonates in vascular calcification in chronic kidney disease? - Hildebrand, S.; Cunningham, J. (Bone (New York, N.Y.), 2021)
Theoretically bisphosphonates could accelerate or retard vascular calcification. In subjects with low GFR, the position is further confounded by a combination of uncertain pharmacokinetics (GI absorption is poor and inconsistent at all levels of renal function and the effect of low GFR generally is to increase bioavailability) and a highly variable skeletal substrate with extremes of turnover that increase unpredictably further. Although bisphosphonates reduce bone formation by 70–90% in subjects with normal GFR and reduce the ability of bone to buffer exogenous calcium fluxes, in bisphosphonate treated postmenopausal women accelerated vascular calcification has not been documented. The kidneys assist with this buffering, but the capacity to modulate calcium excretion declines as GFR falls, increasing the risk of hypercalcaemia in the event of high calcium influx. In the ESRD patient, decreased buffering capacity substantially increases the risk of transient hypercalcaemia, especially in the setting of dialysis, and as such may promote vascular calcification which is highly prevalent in the CKD population. Low bone turnover may thus be less of a vascular problem in patients with preserved renal function and a bigger problem when the GFR is low. In patients with stage 4 and 5 CKD, adynamic bone disease associates with the severity and progression of arterial calcification, including coronary artery calcification, and further suppression of bone turnover by a bisphosphonate might exacerbate an already high predisposition to vascular calcification. No convincing signal of harm has emerged from clinical studies thus far. For example 51 individuals with CKD stage 3–4 treated with either alendronate 70 mg per week or placebo for 18 months showed no difference in the rate of vascular calcifications. Conversely an observational study of women with stage 3–4 CKD with pre-existing cardiovascular disease found an increased risk of mortality with a hazard ratio of 1.22 (1.04–1.42) in those given bisphosphonates. Direct suppression of vascular calcification by bisphosphonates is probably confined to etidronate – treatment of soft tissue calcification was a recognized indication for this drug and etidronate markedly reduced progression of vascular calcification in CKD patients. Bisphosphonates are analogues of pyrophosphate, a potent calcification inhibitor in bone and soft tissue. Thus the efficacy of etidronate as treatment for soft tissue calcification brought with it a problematic tendency to cause osteomalacia. In contrast, conventional doses of nitrogen-containing bisphosphonates fail to yield circulating concentrations sufficient to exert direct anti-calcifying effects, at least in patients with good renal function and studies using alendronate and ibandronate have yielded inconsistent vascular outcomes. •The decreased bone buffering capacity of the kidney in advanced renal disease may lead to medial vascular calcification•Bisphosphonates reduce bone turnover, and with this, reduce calcium flux•The reduction in vascular calcification shown by etidronate has not been replicated by later generation bisphosphonates